2012
DOI: 10.1371/journal.pone.0039242
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Mapping of the Gastrointestinal Microbiota Identifies Children with Inflammatory Bowel Disease

Abstract: BackgroundPediatric inflammatory bowel disease (IBD) is challenging to diagnose because of the non-specificity of symptoms; an unequivocal diagnosis can only be made using colonoscopy, which clinicians are reluctant to recommend for children. Diagnosis of pediatric IBD is therefore frequently delayed, leading to inappropriate treatment plans and poor outcomes. We investigated the use of 16S rRNA sequencing of fecal samples and new analytical methods to assess differences in the microbiota of children with IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
189
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(219 citation statements)
references
References 48 publications
(76 reference statements)
17
189
4
3
Order By: Relevance
“…These predictions remained valid when a subset of samples was reprocessed and reanalyzed in a different hospital. While Papa et al (12) achieved similar accuracy for pediatric IBD predictions, their results indicated that an important factor in diagnostic accuracy was the sequencing depth, which allows low-abundance but highly informative groups to be sampled. This might lead to increased costs, as fewer samples can be analyzed in every run.…”
Section: Figmentioning
confidence: 97%
“…These predictions remained valid when a subset of samples was reprocessed and reanalyzed in a different hospital. While Papa et al (12) achieved similar accuracy for pediatric IBD predictions, their results indicated that an important factor in diagnostic accuracy was the sequencing depth, which allows low-abundance but highly informative groups to be sampled. This might lead to increased costs, as fewer samples can be analyzed in every run.…”
Section: Figmentioning
confidence: 97%
“…Oscillibacter and Lachnospiracea incertae sedis, which are both genera of the Firmicutes phylum and the Clostridia class, were also reduced by sugar. Oscillibacter is negatively correlated with Crohn disease (65,66) and is implicated as a potential treatment for ulcerative colitis after fecal transfer (67). Lachnospiracea incertae sedis are involved in the fermentation of starches to produce SCFAs (68).…”
Section: Figurementioning
confidence: 99%
“…Consistent with this hypothesis, 16S community profiling revealed that the gut microbiome in ERAP-/-did shift, however it was surprisingly towards a more inflammatory profile, with increases of bacteria such as Rikenellaceae, Lachnospiraceae and Ruminococcus which are not only known to elicit a strong immune response, but are also key bacteria in the TI of AS patients (102)(103)(104). The shift in the ERAP-/-mouse microbiome was further explored to determine if it was the overall structure or simply the presence or absence of bacteria that was driving the signature.…”
Section: Discussionmentioning
confidence: 71%
“…Of the seven families of microbes with differences in abundance within the AS microbiome, Lachnospiraceae, Ruminococcaceae and Prevotellaceace are strongly associated with colitis and CD (102)(103)(104) with Prevotellaceace especially known to elicit a strong inflammatory response in the gut (104). Further investigations showed that correlations between these families of bacteria further shape the AS microbial signature, and that these microbes are present in all AS samples studied suggesting that they are not only driving the microbial signature, but they are at the core of the AS microbial signature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation